1943
DOI: 10.1021/ja01246a046
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Lignin and Related Compounds. LXVII. Isolation and Identification of 1-(4-Hydroxy-3,5-dimethoxyphenyl)-2-propanone and 1-(4-Hydroxy-3-methoxyphenyl)-2-propanone from Maple Wood Ethanolysis Products. Metabolic Changes in Lower and Higher Plants

Abstract: Vol. 65 repeated, leaving a viscous tar (D) (25.3 g.). Concentra-tion of the combined petroleum ether solutions (Y', Y", Y'") (water-bath 50-60°), followed by removal of the last traces of solvent under reduced pressure (50°), left a residue of light-colored petroleum ether-soluble ethanolysis oils (43.3 g.) (E).Solvent Group Fractionation of the Petroleum Ethersoluble Ethanolysis Oils.-The petroleum ether-soluble oils (43.3 g.) were dissolved in benzene (300 cc.) and the solution extracted successively with (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1951
1951
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…[6] Only the fraction of the ethers that does not undergo deformylation gives rise to am ixture of the relatively stable Hibbert's ketones. [7] Deuss et al recently demonstrated that loss of monomerst or econdensation could be limited by stoichiometrically trapping intermediate aldehydesf ormed in triflic acid-catalyzed lignin depolymerization, [8] for instanceb ya cetalization with 1,2-ethanediol. Preferably,atrapping strategy does not use sacrificialt rapping reagents, is catalytic, and yields valuablea romatic monomers.…”
mentioning
confidence: 99%
“…[6] Only the fraction of the ethers that does not undergo deformylation gives rise to am ixture of the relatively stable Hibbert's ketones. [7] Deuss et al recently demonstrated that loss of monomerst or econdensation could be limited by stoichiometrically trapping intermediate aldehydesf ormed in triflic acid-catalyzed lignin depolymerization, [8] for instanceb ya cetalization with 1,2-ethanediol. Preferably,atrapping strategy does not use sacrificialt rapping reagents, is catalytic, and yields valuablea romatic monomers.…”
mentioning
confidence: 99%
“…Many suggestions have been advanced to explain the nature of the precursors of lignin (21) and of the mechanism of the synthesis of lignin in the plant. Many suggestions have been advanced to explain the nature of the precursors of lignin (21) and of the mechanism of the synthesis of lignin in the plant.…”
Section: U Studies On Ligninmentioning
confidence: 99%
“…40,46,47,69 Other active stabilisation approaches during acidic fractionation in the lignin-first sphere comprise the rational use of protection-group chemistries. 70,71 Acid-catalysed depolymerization of lignin via acidolysis of the b-O-4 linkage proceeds through two pathways, 72,73 one of which results in the formation of the so called Hibbert's ketones, 74,75 and the other delivers a C2 aldehyde (as mixture of H, G or S, depending on wood), which is unstable under the reaction conditions. Trapping this C2 aldehyde by using diols, typically ethylene glycol, to form more stable cyclic acetals results in suppressing recondensation phenomena and very high selectivity to the corresponding C2-acetals.…”
Section: Introductionmentioning
confidence: 99%